Teachers' and Students' Perceptions of Online Learning Interactions Amidst the COVID-19 Pandemic in Indonesian Senior High Schools - Angen Yudho Kisworo; Oktaviani (IJORER : International Journal of Recent Educational Research, 2021)
The research investigates Indonesian high school teachers' and students' perceptions of learning interactions when the classroom settings were moved online at the beginning of 2020. Conducting this research is essential to unpack the development of online learning after more than a year of pandemic hits in the world. To unload the issue, this research employed a mixed-method design. A survey questionnaire was shared with the teachers around Indonesia, and from this effort, 136 teachers and 107 students agreed to participate in this research. Then, two teachers and two students were chosen to explain in detail their online learning experience. Based on the results, teachers tend to positively perceive online learning, while students moderately perceive the learning. Five interaction aspects influence perceptions: social interaction, instructional interaction, technology interaction, teachers' and students' engagement. The findings suggest that teachers should be more active in enhancing their pedagogical practice and social approach in online classrooms.